2018
DOI: 10.5812/pedinfect.13751
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Pertussis Antibodies in Maternal and Cord Blood Sample of Their Newborns

Abstract: Background: Pertussis is a vaccine-preventable disease that affects infants and adults around the world despite high vaccination coverage. Objectives: The present study was preformed to assess pertussis seroprevalence in maternal serum and cord blood after delivery. Methods: A cross-sectional, descriptive analytical study was carried out in a single urban hospital (Tehran-Iran), during years 2015 and 2016. The target population included term-healthy neonates with their mothers. Immediately after birth, mother'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…There were 8 surveillance studies and 16 serosurveillance studies of pertussis in the Middle East, including Iran [20][21][22][23][24][25][26][27][28][29][30][31][32][33], Israel [34][35][36], Iraq [37], United Arab Emirates (UAE) [38], and Turkey [39][40][41]. An overview of epidemiological/sero-epidemiological studies is shown in Table 1 for Iran and in Table 2 for the other countries with available data.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 8 surveillance studies and 16 serosurveillance studies of pertussis in the Middle East, including Iran [20][21][22][23][24][25][26][27][28][29][30][31][32][33], Israel [34][35][36], Iraq [37], United Arab Emirates (UAE) [38], and Turkey [39][40][41]. An overview of epidemiological/sero-epidemiological studies is shown in Table 1 for Iran and in Table 2 for the other countries with available data.…”
Section: Search Resultsmentioning
confidence: 99%
“…Among 288 pregnant women admitted to hospital in Iran in 2011-2012, 35% were positive for pertussis infection (PT IgG [ 24 IU/ml) [33]. In another study in Iran in 2016-2017, of 88 mothers with a mean age of 29 years, 4.5% had evidence of pertussis infection (PT IgG level unspecified); overall, 81% were vaccinated in childhood suggesting that vaccine-acquired immunity had waned over time [27].…”
Section: Iranmentioning
confidence: 99%